AB0027 Higher percentage of cd3+cd154+t-lymphocytes predicts the efficacy of tnf-a inhibitor in active axial spa. (23rd January 2014) - Lin, Z.; Lin, Q.; Liao, Z.; Li, Q.; Fang, L.; Wei, Q.; Jin, O.; Gu, J.
Abstract : Objectives: To detect the differences of T lymphocyte subtypes between healthy controls and axial Spondyloarthritis (SpA), and evaluate whether certain subtypes of T lymphocytes could be an indicator for predicting clinical efficacy before and after TNF-α inhibitor (Infiximab and Etanercept) treatment (for 12 weeks) in active axial SpA patients. Methods: In this study, patients who fulfilled Assessment of Spondyloarthritis international Society (ASAS) criteria for axial SpA had a Bath Ankylosing Spondylitis(BASDAI) of ≥40mm (VAS=100mm). Data including gender, age, disease duration, onset age, family history, HLA-B27, arthritis, hip involvement and CRP were collected. Thirty-five patients received infliximab (5mg/kg) by intravenous injection at weeks 0, 2, 6, 12, and 39 patients received etanercept by hypodermic injection (50mg once a week ) for 12 weeks. At week 12, ASAS20 was used to evaluate the effect of the treatment. At baseline, 6 ml peripheral blood was obtained from patients and healthy controls to detect the percentage of CD3+CD4+, CD3+CD8+, CD3+CD19+, CD3+CD28+ and CD3+CD154+ T-lymphocytess. Nonparametric test was used to analyze the percentage of subtypes of T-lymphocytes between healthy controls and axial SpA patients. ROC curve analysis was conducted to evaluate whether the percentage of above subtypes of T lymphocytes could predict clinical efficacy. Results: Fifty-eight healthy controls and 74 active axial SpA patients were included. Mean age was 26.28±9.08 years and 26.95±8.13 years for healthy controls and axial SpA patients, respectively (P=0.767). In axial SpA patients, 89.19% (n=66) patients were HLA-B27(+), 14.86% (n=11) patients had positive family history, 34.43% (n=24) had arthritis, 12.16% (n=9) had hip involvement. The percentage of CD3+CD19+ T-lymphocytes on peripheral blood T-lymphocytes was significantly higher in axial SpA patients than in healthy controls (13.04±12.99% vs 8.26±2.59%, p=0.013). Analogously, the percentage of CD3+CD154+ T-lymphocytes on peripheral blood T-lymphocytes was significantly higher in axial patients than in healthy controls (1.62±1.89 vs 0.79±0.52, p=0.000). At baseline, the percentage of CD3+CD154+ T-lymphocytes was significantly higher in HLA-B27(+) patients than HLA-B27(-) ones (HLA-B27+ vs HLA-B27-:1.77±1.95 vs 0.41±0.27, P=0.005). In addition, we found that higher percentage of CD3+CD154+ T-lymphocytes was an indicator to predict satisfactory response for clinical efficacy after ROC curve analysis (AUC=0.733, P=0.014) Conclusions: Higher percentage of CD3+CD19+ and CD3+CD154+ T-lymphocytes was detected in active axial SpA patients than healthy controls. In addition, high-percentage of CD3+CD154+ T-lymphocytes was associated with HLA-B27 positive in axial SpA patients. High-percentage of CD3+CD154+ T-lymphocytes may be a predictive factor of clinical efficacy of TNF-α inhibitor treatment in active axial SpA patients. References: Lin Q, Lin Z, Gu J, Abnormal high-expression of CD154 on T lymphocytes of ankylosing spondylitis patients is down-regulated by etanercept treatment. Rheumatol Int. 2010;30(3):317-23. Disclosure of Interest: None Declared